Optimal carbon policies in a dynamic heterogenous world - Kirill Borissov; Lucas Bretschger (ETH Zurich, CER-ETH - Center of Economic Research, 2018)
We derive the optimal contributions to global climate policy when countries differ with respect to income level and pollution intensity. Countries' growth rates are determined endogenously, and abatement efficiency is improved by technical progress. We show that country heterogeneity has a crucial impact on optimal policy contributions: more developed countries have to make a larger effort while less developed countries are allowed to graduate under a less stringent environmental regime. The optimal allocation of pollution permits depends on international trade. In the absence of international permit trade, more developed countries should receive more permits than the less developed countries but permit prices are higher in the rich countries. With international permit trade, more developed countries receive less permits than the less developed. When global distribution of physical capital is uneven and the aggregate pollution ceiling is low, poor countries receive all the permits and incomes do not converge, even with free trade.
Keywords: Q43; O47; Q56; O41; 330; Climate policy; growth; abatement efficiency; policy convergence